3D bioprinted innervation ADMSC self-clustering culture model constructs for in vitro fat metabolism research: a preliminary study of ADMSC and neural progenitor cell co-culture model construct fabrication and characterization. (December 2022) - Zhang, Y.; Chen, J.W.; Chen, H.Y.; Wang, Z.X.; Li, X.D.; Xu, R.X.; Xu, T.
Abstract: Overweight and obesity influence many people and cause a severe economic burden on healthcare costs worldwide. However, efficient and long-lasting anti-obesity approaches have not been still established, partly owing to the lack of suitable in vitro models. Particularly, since recent advancements have revealed the effect of the abundant innervation in adipose tissue on the thermogenic capacity, the neutralized adipose tissue model for anti-obesity research has been becoming a new research interest. Three-dimensional (3D) bioprinting is a new strategy for fabricating 3D cell-laden model constructs that mimic the structural and functional characteristics of various tissues as well as providing an in vitro model with a similar architecture and microenvironment to the native tissue. Our study aimed to investigate the effect of neural cells integrated into 3D co-axial bioprinted human adipose-derived mesenchymal stem cell (ADMSC)-induced adipose tissue structures on adipogenesis for the fat metabolism research. Compared to 2D and MIX cultures, the bioprinted core-shell constructs provided high cell viability, long-term cell survival, and cell-cell interactions with a suitable physiological microenvironment to support the successful induction of engineered adipose tissue. Moreover, the effect of neural cells integrated into bioprinted constructs was confirmed by small lipid droplets and increased fat metabolism-related proteins in the co-culture of neural cells and ADMSCs compared to the pure culture of ADMSCs. These results suggest that innervation in bioprinted adipose constructs can regulate fat metabolism and provide a promising strategy for the establishment of 3D in vitro models of fat metabolism for medical study on anti-obesity. Graphical abstract: Image 1 Highlights: 3D bioprinted in vitro co-culture core-shell model constructs. To our knowledge, it is the first study to examine the effect of neural cells on fat metabolism based on an in vitro model. Innervation in bioprinted adipose constructs can regulate fat metabolism.